2017
DOI: 10.1097/coc.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for Brain Metastases From Renal Cell Carcinoma in the Targeted Therapy Era

Abstract: This hypothesis-generating analysis suggests among patients with brain metastatic RCC treated with the most current therapies, those selected to undergo SRS did not experience significantly different survival or control outcomes than those selected to undergo WBRT. From our experience to date, limited in patient numbers, there seems to be neither harm nor benefit in using concurrent KI therapy during radiotherapy. Given that most patients progress systemically, we would recommend considering KI use during brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 45 publications
0
33
0
1
Order By: Relevance
“…The role of TT in combination with radiation therapy is currently under investigation. In a retrospective study of the University of Rochester Medical Center, the concurrent use of TT (sunitinib, sorafenib, pazopanib or temsirolimus) with radiotherapy treatment (WBRT, STS or both) was not associated with a statistical increased OS [Bates et al 2015]. Cochran and colleagues showed that TT (TKI, mTOR inhibitors, bevacizumab) improved OS and local control in patients with metastatic RCC (mRCC) treated with GKS when compared with other treatments (chemotherapy or immunotherapy).…”
Section: Targeted Therapy In Combination With Radiotherapymentioning
confidence: 99%
“…The role of TT in combination with radiation therapy is currently under investigation. In a retrospective study of the University of Rochester Medical Center, the concurrent use of TT (sunitinib, sorafenib, pazopanib or temsirolimus) with radiotherapy treatment (WBRT, STS or both) was not associated with a statistical increased OS [Bates et al 2015]. Cochran and colleagues showed that TT (TKI, mTOR inhibitors, bevacizumab) improved OS and local control in patients with metastatic RCC (mRCC) treated with GKS when compared with other treatments (chemotherapy or immunotherapy).…”
Section: Targeted Therapy In Combination With Radiotherapymentioning
confidence: 99%
“…By contrast, SRT with WBRT compared with WBRT alone increases the overall survival of treated patients, indicating that these treatment modalities should be combined. Again when comparing SRS alone with SRT, and SRS with WBRT, the overall survival rate remains the same, however the chance of local recurrence decreases by ~30% when WBRT is added (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Another issue related to WBRT is the potentially increased risk of cognitive function impairment (30).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically if the management should follow the guidelines for surgical resection, which means in the case of renal cell cancer metastasis continuing with observation and waiting to administer systemic treatment only in the case of disease progression or commencing targeted therapy immediately after ablative radiotherapy. No randomized data or recommendations exists regarding this issue and decision should be made on an individual basis (27,40).…”
Section: Discussionmentioning
confidence: 99%
“…However, retrospective studies of the additional impact of TKI on local control and survival have conflicting findings [ 45 , 76 , 77 , 78 , 79 ]. Three studies retrospectively compared BM patients treated by brain RT (SRS or WBRT) with or without TKI [ 45 , 76 , 77 ].…”
Section: Treatment Strategy Against Rcc-bmmentioning
confidence: 99%
“…However, retrospective studies of the additional impact of TKI on local control and survival have conflicting findings [ 45 , 76 , 77 , 78 , 79 ]. Three studies retrospectively compared BM patients treated by brain RT (SRS or WBRT) with or without TKI [ 45 , 76 , 77 ]. Bates et al suggested that concurrent TKI use was not associated with any change in OS or local control, but their analysis included only 25 patients [ 76 ]; whereas Cochran suggested that combining TKI with local therapy improved local control and extended median OS (targeted therapy: 16.6 months [ n = 24], no targeted therapy: 7.2 months [ n = 37]; p = 0.04) and lower local failure at one year (targeted therapy: 93%, no targeted therapy: 60%; p = 0.01) [ 77 ].…”
Section: Treatment Strategy Against Rcc-bmmentioning
confidence: 99%